JAPANESE IDIOMS USE LIMBS THEIR MEANING OF DECLARATION NATURE AND BEHAVIOR - M Rival; Syahrial; Diana Kartika; Tienn Immerry (Program Studi Sastra Jepang Fakultas Ilmu Budaya Universitas Bung Hatta, 2023)
Expressive expressions that cannot be explained logically or grammatically are called idioms. Types of idioms based on their constituent elements are divided into six types, namely idioms with names of body parts, colors, animals, plants, numbers, and natural objects. Then based on the type of meaning, idioms are divided into five types, namely idioms that express feelings/senses, nature or behavior, actions or activities, degrees or values, and the life of society or culture. The purpose of this research is to describe the meaning idiomatical idioms of the body that express nature and behavior. The method used is method qualitative descriptive. The results of this study are Japanese idioms using limbs that are found as many as 24 data, 11 idiom data which states the nature and 13 idiom data which states the behavior.